Współdecydowanie w Euroregionie Sprewa-Nysa-Bóbr = The inhabitant participation in the functioning of the Sprewa-Nysa-Bóbr Euroregion - Mielczarek-Żejmo, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to describe the participation of the inhabitants of the Sprewa-Nysa-Bobr Euroregion (SNBE) in shaping its activities. The research questions concerned communication strategies in the Euroregion, the position occupied by the inhabitants in its organisational structure, and the assessment of its functioning. The presented analysis is based on the research conducted between 2013 and 2014, which included: a survey involving the quota sample of 400 Polish and 200 German inhabitants of the SNBE, in-depth interviews with 70 leaders in cross-border cooperation, and the analysis of documentation (documents of the SNBE, analysis of the website). In conclusions, the author notes that the possibilities of shaping the Euroregion activities are not fully used. This results from the fact that neither inhabitants nor activists in the SNBE are interested in co-deciding.
Keywords: Euroregiony; partycypacja obywatelska; współrządzenie; Euroregion; citizens` participation; co-governing